ANTIBIOTIC SENSITIVITY AND RESISTANCE PATTERN IN ORTHOPEDIC INFECTIOUS CASES OF A TERTIARY CARE TEACHING HOSPITAL: Pharmaceutical Sciences-Pharmacology - VALYA, B.; KR. DAS, SUSHANTA; KAVYA, T.; VIDYASAGAR, VADLA; BEGUM, RUBINA (International Journal of Life Science and Pharma Research, 2017)
Aim of this study was to evaluate the antibiotic resistance and sensitivity pattern in various orthopedic infectious cases. Study conducted upon patients present with orthopedic infection and post operative surgical site infection present in orthopedic in-patient during August 2016 to October 2016. Bacterial culture investigation was carried out to identify the specific organism present. Antibiotic sensitivity profile was obtained by “Kirby-Bauer disc diffusion” method from hospital microbiology lab. Relevant data was collected from patient medical report and was analyzed to get the final outcome. A total of 16 infectious cases were confirmed and reported during the study period. Of these 16 cases, male preponderance (15) with age group 21-30 years (05). Out of 16 cases, 13 were surgical site infection, 02 osteomyelytis and only 01 septic arthritis case. Most frequently isolated organism was Staphylococcus aureus (07) followed by Eschericia coli (04) (43.75%). Maximum isolated organism shows resistance to Amoxicillin+Clavulanic acid combination. In orthopedic infectious cases, culture and sensitivity report offers a better support to choose appropriate antibiotic so as to get better outcome with minimal treatment failure.